Pengaruh Digital Distraction, Beban Kerja, Dan Tingkat Stres Terhadap Kinerja Akademik Mahasiswa Kelas Karyawan Universitas Pamulang - Ria Mutiara Diandra; Hitung Nius Halawa; Ahmad Abdul Mujib; Minta Syukur Zega; Ria Aulia (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the effect of digital distraction, workload, and stress level on the academic performance of working students in the employee class program at Universitas Pamulang, both partially and simultaneously. This study employed a quantitative approach with an associative research design. Data were collected through a Likert-scale questionnaire distributed to 101 active working students selected using a non-probability purposive sampling technique, and were subsequently analyzed using multiple linear regression with the assistance of IBM SPSS Statistics version 26. The classical assumption tests indicate that the regression model is normally distributed and free from multicollinearity and heteroscedasticity, making it suitable for hypothesis testing. The partial hypothesis test (t-test) results show that digital distraction (t = -5.655; Sig. = 0.000), workload (t = -2.836; Sig. = 0.005), and stress level (t = -5.670; Sig. = 0.000) each have a negative and significant effect on academic performance. The simultaneous test (F-test) yields an F value of 64.524 (Sig. = 0.000 < 0.05), indicating that the three independent variables jointly have a significant effect on the academic performance of working students. These findings suggest that higher levels of digital distraction, workload, and psychological stress experienced by working students are associated with lower academic performance. This study offers practical implications for students, educational institutions, and employers to develop time-management strategies, digital literacy, and stress-management interventions to support the academic success of students who play the dual role of employee and learner.